Method for producing aluminum-containing alloy powder and its use, and alloy ribbon
The primary aluminum alloy belt is formed by curing the aluminum alloy primary melt of a specific composition, and the pure aluminum alloy powder is separated by acid solution reaction, which solves the problems of low production efficiency, high cost and difficult to control purity in the existing methods, and realizes the single crystal structure and large-scale production of high-purity aluminum alloy powder.
Patent Information
- Application Number
- JP2023120253
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-13
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-11-23
AI Technical Summary
The existing methods have problems such as low production efficiency, high cost, difficult to control purity, difficulty in sorting powder, and oxygen content affecting performance when producing aluminum alloy powder. The existing methods have strong selectivity for raw materials, making it difficult to achieve industrial production of high-purity aluminum alloy powders.
The aluminum alloy primary melt of a specific composition is used to form a primary aluminum alloy belt through melting and curing, and the pure aluminum alloy powder is separated by acid solution reaction to ensure the high purity and single crystal structure of the aluminum alloy powder. A strip-shaped aluminum alloy belt is used for large-scale production.
It realizes high-purity and low-cost aluminum alloy powder production, ensuring the single crystal structure and efficient classification of the powder, and is suitable for a variety of application fields.
Smart Images

Figure 0007627968000001 
Figure 0007627968000002 
Figure 0007627968000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of metallic materials technology, in particular to a method for producing and using an aluminum-containing alloy powder, as well as to an alloy ribbon. [Background technology]
[0002] There are many methods for producing alloy powder, but each method has certain limitations. For example, the disadvantages of the liquid phase method are low production volume, high cost, and complicated process. The disadvantages of the mechanical method are that it is difficult to classify the powder after production, and it is difficult to guarantee the purity, fineness, and morphology of the product. The rotating electrode method and the gas atomization method are currently the main methods for producing high-performance alloy powder, but they have low production efficiency and relatively large energy consumption. The jet mill method and the hydrogenation and dehydrogenation method are suitable for large-scale industrial production, but they are highly selective for the raw metals and alloys. In addition, the content of impurities in metal powder or alloy powder, especially the oxygen content, has a very large impact on its performance. In the past, the content of impurities in metal powder or alloy powder was mainly controlled by controlling the purity of the raw materials and the degree of vacuum, but the cost is high. Therefore, it is of great significance to develop a new method for producing high-purity alloy powder materials. Summary of the Invention
[0003] Based on this, it is necessary to provide a method for producing an aluminum-containing alloy powder and its use in order to meet the above-mentioned objectives.
[0004] The method for producing an aluminum-containing alloy powder comprises the steps of: Step 1: Selecting an initial alloy raw material, melting the initial alloy raw material according to the blending ratio of the initial alloy components, and obtaining a homogeneous initial alloy melt; a Al b M c T dRE includes at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, and Ni; and T is an impurity element and at least one of O, H, N, P, S, F, and Cl. Consists of Step 1, wherein a, b, c, and d represent the atomic mass percentage contents of the corresponding composition elements, and are 35%≦a≦99.7%, 0.1%≦b≦25%, 0.1%≦c≦35%, and 0≦d≦10%; Step 2 is to solidify the initial alloy melt into an initial alloy ribbon, the solidification structure of the initial alloy ribbon includes a matrix phase and a dispersed particle phase, the melting point of the matrix phase is lower than that of the dispersed particle phase, the dispersed particle phase is coated with the matrix phase, and the average component of the matrix phase is mainly RE. x1 Al y1 T z1 The dispersed particle phase is mainly composed of M x2 Al y2 T z2 Wherein x1, y1, z1, x2, y2, z2 represent the atomic mass percentage contents of the corresponding composition elements, and 60%≦x1<99.8%, 0.2%≦y1≦30%, 0.05 ≦z1≦30%, 80%≦x2≦99.8%, 0.1%≦y2≦22%, 0.05 ≦z2≦1.5%, z2≦d≦z1, and during the solidification process of the initial alloy melt, the impurity element T in the initial alloy melt is redistributed between the dispersed particle phase and the matrix phase and enriched in the matrix phase, thereby purifying the dispersed particle phase; The initial alloy ribbon is reacted with an acid solution, and the matrix phase in the initial alloy ribbon reacts with the acid to become ions and enter the solution, while the dispersed particle phase that does not react with the acid solution is detached from the initial alloy ribbon, and the main component is M x2 Al y2 T z2 Step 3 of obtaining an aluminum-containing alloy powder material, The present invention is characterized by comprising:
[0005] In the above step 1, Furthermore, the origin of the impurity elements in the initial alloy melt includes impurities introduced from the initial alloy raw materials and impurities introduced from the atmosphere or crucible during the smelting process, where the impurities introduced from the atmosphere refer to impurities such as O, N, and H absorbed by the alloy melt from the surrounding atmosphere.
[0006] Furthermore, the initial alloy raw material includes an MT raw material containing an impurity element T. For example, when M is Ti and T contains O, the MT raw material is, that is, a Ti-O raw material containing O impurity.
[0007] Furthermore, T is an impurity element and includes at least one of O, H, N, P, S, F, and Cl, and the total content of these impurity elements is the content of the T impurity element.
[0008] Further, preferably, 0 <d≦10%である。 Furthermore, preferably, the above-mentioned M contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, and Ni, and when M contains at least one of Fe, Co, and Ni, it also simultaneously contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti.
[0009] More preferably, the M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti.
[0010] In the above step 2, Furthermore, the initial alloy ribbon does not contain any intermetallic compound composed of RE and M.
[0011] Furthermore, the methods for solidifying the molten alloy include strip casting and continuous casting. Generally, the strip casting method can produce a thin initial alloy ribbon, while the continuous casting method can produce a thick alloy ribbon.
[0012] Whether the thin alloy ribbon obtained by strip casting or the thick alloy ribbon obtained by continuous casting is obtained, the morphology is completely different from that of the alloy ingot obtained by ordinary casting, and the length / thickness ratio of the alloy ingot obtained by ordinary casting is generally not obvious.
[0013] Furthermore, the thickness range of the initial alloy ribbon is 5 μm to 50 mm, further, the thickness range of the initial alloy ribbon is 5 μm to 5 mm, preferably, the thickness range of the initial alloy ribbon is 5 μm to 1 mm, even more preferably, the thickness range of the initial alloy ribbon is 5 μm to 200 μm, and even more preferably, the thickness range of the initial alloy ribbon is 5 μm to 20 μm.
[0014] When the thickness of the initial alloy ribbon is on the order of millimeters, it may be referred to as a thin alloy plate.
[0015] Additionally, the cross-sectional width of the initial alloy ribbon is at least twice its thickness.
[0016] Additionally, the length of the initial alloy ribbon is at least 10 times its thickness.
[0017] Preferably, the length of said initial alloy ribbon is at least 50 times its thickness.
[0018] Preferably, the length of said initial alloy ribbon is at least 100 times its thickness.
[0019] Furthermore, the solidification rate of the initial alloy melt is 1K / s to 10 7 K / s.
[0020] Furthermore, the particle size of the dispersed particle phase is related to the solidification rate of the initial alloy melt. In general, the particle size of the dispersed particle phase has a negative correlation with the solidification rate of the initial alloy melt, i.e., the higher the solidification rate of the initial alloy melt, the smaller the particle size of the dispersed particle phase.
[0021] Further, the particle size range of the particles of the dispersed particle phase is 2 nm to 3 mm, and further, the particle size range of the particles of the dispersed particle phase is 2 nm to 500 μm, preferably, the particle size range of the particles of the dispersed particle phase is 2 nm to 99 μm, even more preferably, the particle size range of the particles of the dispersed particle phase is 2 nm to 5 μm, even more preferably, the particle size range of the particles of the dispersed particle phase is 2 nm to 200 nm, and even more preferably, the particle size range of the particles of the dispersed particle phase is 2 nm to 100 nm.
[0022] Furthermore, the solidification rate of the initial alloy melt is 10 5 K / s~10 7 When the particle size is 100 K / s, dispersed particles having a particle size mainly on the nano order are obtained.
[0023] Furthermore, the solidification rate of the initial alloy melt is 10 4 K / s~10 5 When the concentration is 100 K / s, dispersed particles having particle sizes mainly on the submicron order are obtained.
[0024] Furthermore, the solidification rate of the initial alloy melt is 10 2 K / s~10 4 K / s, dispersed particles having particle sizes mainly on the order of microns are obtained.
[0025] Furthermore, the solidification rate of the initial alloy melt is 1K / s to 10 2 K / s, dispersed particles having particle sizes mainly on the order of millimeters are obtained.
[0026] Furthermore, the shape of the particles of the dispersed particle phase is not limited and may include at least one of dendritic, spherical, nearly spherical, rectangular, discoid, and rod-shaped, and when the particle shape is rod-shaped, the particle dimensions refer specifically to the diameter of the cross section of the rod.
[0027] Furthermore, the dispersed particle phase solidifies and precipitates from the initial alloy melt, and according to nucleation and growth theory, whether it is a nucleation-grown, roughly spherical nanoparticle or a fully grown, micron- or millimeter-order dendritic particle, the growth of the crystal has a certain orientation relationship, so that each precipitated single particle is mainly composed of one single crystal.
[0028] When the volume percentage content of the above-mentioned dispersed particles in the entire initial alloy ribbon is high, it is not excluded that two or more particles will be bonded together during the intrinsic precipitation process of the single crystal particles. If two or more single crystal particles are weakly agglomerated, adsorbed to each other, or only bonded at a few sites in contact with each other, and are not fully bonded to form one particle by normal grain boundaries like polycrystalline materials, they are still two single crystal particles. The characteristic is that after the matrix phase is removed in the later process, these single crystal particles are easy to separate by techniques including ultrasonic dispersion treatment, jet mill grinding, etc. However, it is difficult to separate the grain boundaries of normal ductile metal or alloy polycrystalline materials by techniques including ultrasonic dispersion treatment, jet mill grinding, etc.
[0029] Preferably, the number of single crystal particles among the dispersed particles in the initial alloy ribbon is 75% or more of the total number of dispersed particles.
[0030] More preferably, the number of single crystal particles among the dispersed particles is 90% or more of the total number of dispersed particles.
[0031] Further, the volume percentage content of the dispersed particle phase is 40% or less relative to the initial alloy ribbon.
[0032] Furthermore, c≦35%, and the RE elements are mainly large-atom rare earth elements, whose atomic weights are generally higher than that of the M elements. Therefore, when the atomic mass percentage content of the M elements is controlled to be 35% or less in the alloy melt, the volume percentage content of the dispersed particle phase mainly composed of the M elements is also generally 35% or less.
[0033] Furthermore, the average component of the above Al element is mainly RE x1 Al y1 T z1 The atomic mass percentage content of the matrix phase, where the component is mainly M x2 Al y2 T z2 is higher than the atomic mass percentage content with respect to the dispersed particle phase where the component is mainly M
[0034] Furthermore, z2 has a lower atomic mass percentage content than the T impurity element in the M-T raw material, that is, the above main component is M x2 Al y2 T z2 The atomic mass percentage content of the T impurity element in the dispersed particle phase, where the component is mainly M
[0035] Furthermore, z2 ≤ d ≤ z1, and 2z2 ≤ z1 Preferably, z2 ≤ d ≤ z1, and 3z2 ≤ z1 Furthermore, z2 ≤ d ≤ z1, 3z2 ≤ z1, and 0 ≤ z2 ≤ 1.5% Preferably, 0 < z2 < d < z1, 3z2 < z1, and 0 < z2 ≤ 1.5%, that is, the content of the T impurity in the above dispersed particle phase is lower than the content of the T impurity in the above initial alloy melt, and three times the content of the T impurity in the above dispersed particle phase is still lower than the content of the T impurity in the above matrix phase
[0036] Preferably, 68% ≤ x1 < 99.7%, 0.2% ≤ y1 ≤ 30%, 0 < z1 ≤ 30%, 77% ≤ x2 ≤ 99.8%, 0.1% ≤ y2 ≤ 22%, 0 < z2 ≤ 1.5%, and z2 < d < z1 More preferably, 0 < z2 < d < z1, 3z2 < z1, and 0 < z2 ≤ 0.75%
[0037] The present invention expresses the content of T impurity in terms of atomic mass percentage content. By characterizing the composition of each element by the atomic mass percentage content of the element, the increase / decrease and change of element content, such as the increase / decrease and change of impurity elements, can be correctly expressed in terms of the concept of the amount of substance. If the content of each element is characterized by the mass percentage content of the element (or ppm concept), it is easy to draw erroneous conclusions because the atomic weight of each element is different. For example, if the atomic mass percentage content of Ti 45 Gd 45 O 10 An alloy containing 100 atoms has an atomic mass percentage content of O of 10 at%. 45 O 4 (Atomic mass percentage composition is Ti 91.8 O 8.2 ) and Gd 45 O 6 (Atomic mass percentage composition is Gd 88.2 O 11.8 If we divide it into two parts, Gd 45 O 6 The atomic mass percentage content of oxygen in Ti increased to 11.8 at%. 45 O 4 The atomic mass percentage content of oxygen in Gd is reduced to 8.2 at%, which can be used to correctly represent the enrichment of O in Gd. However, if the mass percentage content of O is used, the Ti 45 Gd 45 O 10 The mass percentage content of O in the 45 O 4 and Gd 45 O 6 The mass percentage contents of O in the 45 O 4 The O content in Gd 45 O 6 This leads to the erroneous conclusion that the O content in the solution is significantly increased compared to the O content in the solution.
[0038] In the above step 3, Furthermore, the acid in the acid solution includes at least one of sulfuric acid, hydrochloric acid, nitric acid, perchloric acid, phosphoric acid, acetic acid, oxalic acid, formic acid, and carbonic acid.
[0039] Furthermore, the molar concentration of the acid is 0.01 mol / L to 10 mol / L.
[0040] Furthermore, the reaction temperature between the initial alloy ribbon and the acid solution is 0° C. to 100° C., and the reaction time is 0.1 min to 24 h.
[0041] Furthermore, the particles of the aluminum-containing alloy powder material have a particle size range of 2 nm to 3 mm.
[0042] Preferably, the particles of the aluminum-containing alloy powder material have a particle size in the range of 2 nm to 500 μm.
[0043] Preferably, the particles of the aluminum-containing alloy powder material have a particle size range of 2 nm to 99 μm.
[0044] More preferably, the particles of the aluminum-containing alloy powder material have a particle size in the range of 2 nm to 10 μm.
[0045] More preferably, the particles of the aluminum-containing alloy powder material have a particle size in the range of 2 nm to 1 μm.
[0046] More preferably, the particles of the aluminum-containing alloy powder material have a particle size in the range of 2 nm to 200 nm.
[0047] More preferably, the particles of the aluminum-containing alloy powder material have a particle size in the range of 2 nm to 100 nm.
[0048] Furthermore, after reacting the initial alloy ribbon with the acid solution, the dispersed particles are detached from the initial alloy ribbon, washed and dried, and the main component is M. x2 Al y2 T z2 Thus, an aluminum-containing alloy powder material is obtained,
[0049] Furthermore, after the above step 3, a step is performed in which the above aluminum-containing alloy powder material is screened, and then aluminum-containing alloy powder material having a particle size range of 5 μm to 200 μm is selected and subjected to plasma spheroidization treatment to obtain spherical aluminum-containing alloy powder material.
[0050] Furthermore, the particle size of the spherical aluminum-containing alloy powder is in the range of 5 μm to 200 μm.
[0051] Furthermore, the present invention relates to the use of the aluminum-containing alloy powder or spherical aluminum-containing alloy powder material obtained by the above-mentioned production method in optoelectronic devices, electromagnetic wave absorbing materials, catalysts, powder metallurgy, three-dimensional metal printing, metal injection molding, and paints.
[0052] Furthermore, the spherical aluminum-containing alloy powder material obtained by the above manufacturing method is used in the field of three-dimensional printing using metal powder, characterized in that the particle size of the spherical aluminum-containing alloy powder is 5 μm to 200 μm.
[0053] Furthermore, the aluminum-containing alloy powder or the spherical aluminum-containing alloy powder obtained by the above-mentioned production method is used in metal injection molding and powder metallurgy, characterized in that the particle size of the aluminum-containing alloy powder or the spherical aluminum-containing alloy powder is 0.1 μm to 50 μm.
[0054] Furthermore, the present invention relates to a use of the aluminum-containing alloy powder obtained by the above-mentioned production method in a paint, characterized in that the particle size of the aluminum-containing alloy powder is 2 nm to 5 μm.
[0055] The present invention further relates to an alloy ribbon, comprising an endogenous aluminum-containing alloy powder and a cladding, the solidification structure of the alloy ribbon comprises a matrix phase and a dispersed particle phase, the matrix phase is the cladding, the dispersed particle phase is the endogenous aluminum-containing alloy powder, the melting point of the cladding is lower than that of the endogenous aluminum-containing alloy powder, the endogenous aluminum-containing alloy powder is coated with the cladding, and the average composition of the cladding is mainly RE.x1 Al y1 T z1 The main component of the intrinsic aluminum-containing alloy powder is M x2 Al y2 T z2 Wherein x1, y1, z1, x2, y2, z2 represent the atomic mass percentage contents of the corresponding composition elements, and 60%≦x1<99.8%, 0.2%≦y1≦30%, 0.05 ≦z1≦30%, 80%≦x2≦99.8%, 0.1%≦y2≦22%, 0.05 ≦z2≦1.5%, z2≦z1, y1>y2, the RE includes at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, and Ni, and T is an impurity element and includes at least one of O, H, N, P, S, F, and Cl. Consists of It is characterized by:
[0056] Preferably, the M contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, and Ni, and when M contains at least one of Fe, Co, and Ni, it also contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti.
[0057] More preferably, the M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti.
[0058] Furthermore, the thickness range of the alloy ribbon is 5 μm to 50 mm.
[0059] Preferably, the thickness of the alloy ribbon is in the range of 5 μm to 5 mm.
[0060] Preferably, the thickness of the alloy ribbon is in the range of 5 μm to 1 mm.
[0061] More preferably, the thickness of the alloy ribbon is in the range of 5 μm to 200 μm.
[0062] More preferably, the thickness of the alloy ribbon is in the range of 5 μm to 20 μm.
[0063] Additionally, the alloy ribbon cross-section has a width greater than or equal to twice its thickness.
[0064] Additionally, the length of the initial alloy ribbon is at least 10 times its thickness.
[0065] Preferably, the length of said initial alloy ribbon is at least 50 times its thickness.
[0066] Preferably, the length of said initial alloy ribbon is at least 100 times its thickness.
[0067] Furthermore, the particle size of the intrinsic aluminum-containing alloy powder particles is in the range of 2 nm to 3 mm.
[0068] Preferably, the intrinsic aluminum-containing alloy powder particles have a particle size range of 2 nm to 500 μm.
[0069] Preferably, the intrinsic aluminum-containing alloy powder particles have a particle size range of 2 nm to 99 μm.
[0070] More preferably, the particle size of the intrinsic aluminum-containing alloy powder particles is in the range of 2 nm to 10 μm.
[0071] More preferably, the particle size of the intrinsic aluminum-containing alloy powder particles is in the range of 2 nm to 1 μm.
[0072] More preferably, the particle size of the intrinsic aluminum-containing alloy powder particles is in the range of 2 nm to 200 nm.
[0073] More preferably, the particle size of the intrinsic aluminum-containing alloy powder particles is in the range of 2 nm to 100 nm.
[0074] Furthermore, the particle shape of the intrinsic aluminum-containing alloy powder includes at least one of dendritic, spherical, nearly spherical, rectangular, discoid, and rod shapes.
[0075] Furthermore, the number of single crystal particles among the intrinsic aluminum-containing alloy powder in the alloy ribbon is 75% or more relative to the total number of the intrinsic aluminum-containing alloy powder.
[0076] Furthermore, the volume percentage content of the intrinsic aluminum-containing alloy powder relative to the alloy ribbon is less than 40%.
[0077] Further, 2z2≦z1 and 0≦z2≦1.5%, Preferably, 3z2 <z1、かつ0<z2≦1.5%であり、 Preferably, 68%≦x1<99.7%, 0.2%≦y1≦30%, 0 <z1≦30%、77%≦x2≦99.8%、0.1%≦y2≦22%、0<z2≦1.5%、z2<d<z1であり、 More preferably, 3z2 <z1、かつ0<z2≦0.75%である。
[0078] In addition, the above A, M, or T may further contain other elements or impurity elements other than the above-listed elements. As long as the introduction or change in the content of these elements does not result in a "qualitative change" in the initial alloy solidification process and rules, the realization of the above technical solution of the present invention will not be affected.
[0079] Specifically, the absence of a "qualitative change" in the above initial alloy solidification process and rules means that when A, M or T contains elements or impurity elements other than those listed above, the factual processes and rules listed in 1) to 3) below still exist. 1) The initial alloy ribbon does not contain any intermetallic compounds mainly composed of RE and M. 2) The solidification structure of the initial alloy ribbon includes a matrix phase and a dispersed particle phase, the melting point of the matrix phase is lower than that of the dispersed particle phase, and the dispersed particle phase is covered by the matrix phase. 3) When the content of T impurity in the initial alloy melt is not 0, the content of T impurity in the dispersed particle phase is lower than the content of T impurity in the initial alloy melt, and twice the content of T impurity in the dispersed particle phase is still lower than the content of T impurity in the matrix phase.
[0080] The technical solution described in the present invention has the following beneficial effects: First, the solid solution of Al element in metal or alloy material containing elements such as W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, Ni, etc. is realized. The addition of Al element to the above alloy material has a very important effect. For example, the most widely used titanium alloy in the past is Ti6Al4V alloy. For Ti6Al4V alloy powder, Ti6Al4V alloy melt is generally smelted, and then Ti6Al4V alloy powder is obtained by atomization milling technology. Due to the limitations of atomization milling technology, it is very difficult to obtain ultra-fine Ti6Al4V alloy powder, and even nano-order Ti6Al4V alloy powder cannot be obtained by atomization milling technology. Therefore, it is very significant to realize the addition of Al element to Ti-V alloy by the "dephasing method" of the present invention and to produce Ti6Al4V alloy powder of various particle sizes. The present invention successfully finds that when a significant content of Al element is added to an alloy with RE-M composition (may be 10 at.% or more), the Al element in the alloy solidification structure can exist simultaneously in a matrix phase mainly composed of RE and a dispersed particle phase mainly composed of M according to a certain content distribution relationship. The RE-Al matrix phase is very easy to be removed by acid reaction, and the Al in the Al-containing dispersed particles mainly composed of M is protected by the inert M element and is difficult to be removed by acid reaction (for example, Ti6Al4V alloy has very good acid corrosion resistance ability), so that the matrix phase can be removed by acid reaction to produce an aluminum-containing titanium alloy powder.
[0081] Next, by the ingenious element selection, it is ensured that no intermetallic compound composed of RE and M is formed in the initial alloy ribbon, and the alloy particles containing aluminum and M as the target component can be formed during the solidification process of the initial alloy melt, and can be separated by a later process. The present invention selects metal M containing impurity T, metal Al, and rare earth RE to obtain a material containing RE as the main component. a Al b M c T d The initial alloy melt is smelted. The solidification structure of the initial alloy melt is x2 Al y2 T z2 The dispersed particle phase is mainly composed of RE and the average component is mainly composed of RE. x1 Al y1 T z1 The solidification structure is advantageous for the dispersed particle phase to be separated by the reaction between the initial alloy ribbon and the acid solution. Specifically, when the initial alloy ribbon reacts with the acid solution, the hydrogen ions in the acid solution react with the RE and Al elements in the matrix phase, and the RE and Al elements dissolve and enter the solution as ions. x2 Al y2 T z2 The Al dissolved in the dispersed particle phase is protected by the inert element M and does not react easily with the acid solution. x2 Al y2 T z2 The dispersed particle phase, which is the matrix phase, can be dispersed and removed after it reacts with the acid solution and is removed. x2 Al y2 T z2 The aluminum-containing alloy powder is obtained by cooling the initial alloy ribbon at different rates. x2 Al y2 T z2 The size of the dispersed particle phase may be on the order of nanometers, submicrometers, micrometers, or even millimeters, and the particle size of the aluminum-containing alloy powder produced thereby may also be on the order of nanometers, submicrometers, micrometers, or even millimeters.
[0082] Third, an aluminum-containing alloy powder mainly composed of single crystal particles is obtained. Compared with polycrystalline powder, single crystal powder can provide many significant and beneficial effects. During the solidification process of the initial alloy melt, each endogenous dispersed particle is nucleated at a certain position in the melt and then grows and forms according to a specific atomic arrangement. When the volume percentage content of the matrix phase is controlled to allow each endogenous particle to be dispersed, the endogenous particles are unlikely to grow together. Therefore, the finally obtained dispersed particle phase is mostly a single crystal phase. Even if the scale of the dendrite particles is tens of microns or millimeters, the growth direction of each secondary dendrite is in a certain phase relationship with the growth direction of the main dendrite, and each belongs to a single crystal particle. For polycrystalline materials, the grain boundaries are generally prone to contain impurity elements discharged from the crystal during the solidification process, so it is very difficult to obtain high-purity polycrystalline powder materials. In addition, when the powder material is mainly composed of single crystal particles, its purity is guaranteed. In addition, the atoms on the surface of the single crystal particles have a specific arrangement, such as a (111) plane arrangement, and these specific arrangements give the single crystal powder material special mechanical, physical, and chemical properties, which can produce beneficial effects.
[0083] Fourth, it is possible to obtain high purity aluminum-containing alloy powder from low purity raw materials, which points out a new route for the production of high purity metal powder materials from low purity raw materials and has positive significance. The improvement of the purity of the high purity aluminum-containing alloy powder of the present invention is mainly achieved through the following two mechanisms: 1) The "absorption" effect of RE rare earth elements on impurity elements in the initial alloy melt. Because there is an extremely strong affinity between the selected RE rare earth element and the impurity element T, a larger amount of the impurity element T in the initial alloy melt enters the matrix phase mainly composed of the RE element, or forms slag with the RE rare earth element in the molten state, and is separated and removed together with the alloy melt. 2) During the nucleation and growth process of the aluminum-containing intrinsic alloy powder (intrinsically precipitated dispersed particle phase), the impurity element T is discharged into the remaining melt. If the aluminum-containing intrinsic alloy powder is not slower than the precipitation of the matrix phase during the solidification process, the impurity will be enriched in the melt of the last part to solidify, i.e., the part of the melt that is mainly composed of RE rare earth elements and solidifies to form the matrix phase. As a result of the two mechanisms, the impurity element T is enriched in the matrix phase that is mainly composed of RE rare earth elements, refining the aluminum-containing intrinsic dispersed particle phase. In addition, due to the presence of the second phase matrix, the crucible-related impurities that enter the melt due to the interaction between the crucible and the melt during the smelting process are generally also concentrated in the second phase matrix, further reducing the content of impurities in the aluminum-containing alloy powder, further reducing the requirements for the crucible during the smelting process, and significantly reducing the production cost.
[0084] Fifth, the alloy ribbon composed of the endogenous aluminum-containing alloy powder and the coating body has a matrix phase formed in situ that encases the endogenous aluminum-containing alloy powder, thereby maintaining the high purity and high activity of the endogenous aluminum-containing alloy powder. Specifically, metal or alloy powders produced by conventional chemical and physical methods, especially nanopowder with a very large specific surface area, are very prone to natural oxidation, and the powder is difficult to store. In response to this problem, one technical solution in the present invention is to use the coating body as it is after producing the alloy ribbon composed of the endogenous aluminum-containing alloy powder and the coating body, rather than hastily removing the coating body, to prevent the endogenous aluminum-containing alloy powder from being naturally oxidized. Such an alloy ribbon composed of the endogenous aluminum-containing alloy powder and the coating body can be used as a raw material in downstream production, and has the potential to become a special product. When high purity endogenous aluminum-containing alloy powder needs to be used in downstream production, the endogenous aluminum-containing alloy powder is released from the coating in the alloy ribbon by acid solution at a suitable time and under a suitable environment according to the characteristics of the following processes, and the released endogenous aluminum-containing alloy powder is allowed to enter the next production process within a short time as possible, so as to greatly reduce the chance of the aluminum-containing alloy powder being contaminated by impurities such as oxygen. For example, when the endogenous aluminum-containing alloy powder is nanopowder, the aluminum-containing alloy powder is compounded with resin at the same time or immediately after it is released from the coating to produce a resin-based composite material containing aluminum-containing nano-alloy powder with high activity.
[0085] Sixth, in the above step 2, the solid alloy obtained by solidification is in the form of a ribbon, which ensures the uniformity of the product shape and the feasibility of large-scale production. If the alloy ribbon is a thin alloy ribbon, it can be produced by a strip casting method. By maintaining a constant flow rate of the alloy melt flowing to the rotating roll and a constant rotation speed of the rotating roll, a thin alloy ribbon with a uniform thickness can be obtained, and the production process can be carried out continuously, which is advantageous for large-scale production. If the alloy ribbon is a thick alloy ribbon, it can be produced by a well-established continuous casting method. The principle of continuous casting is similar to that of strip casting, and the melt can be used to obtain a continuous thin ribbon with a uniform thickness. The production process can be carried out continuously, which is advantageous for large-scale production. If the thickness of the alloy ribbon is uniform, the cooling speed is also uniform, and the particle size of the obtained dispersed particles is also uniform. In contrast, when the solid alloy obtained by solidification is in the form of an ingot, common knowledge tells us that the ingot does not have a uniform thickness, does not have a clear length, and generally makes it difficult for the internal melt to dissipate heat, which makes it easy to obtain abnormally large intrinsic particles, and such an operation is only necessary when it is simply necessary to collect and refine the large intrinsic particles. Therefore, the present invention is suitable for obtaining an alloy ribbon by solidification, and then using the "dephasing method" to produce an aluminum-containing alloy powder material.
[0086] Therefore, the manufacturing process of the present invention is simple, easy to operate, and low cost, and can produce high-purity aluminum-containing alloy powders with different morphologies in the nano-order, submicron-order, micron-order, and milli-order sizes, which has great potential for use in the fields of optoelectronic devices, electromagnetic wave absorbing materials, catalysts, powder metallurgy, three-dimensional metal printing, metal injection molding, coatings, etc.
[0087] Alternatively, the present invention provides a method for producing a cellular membrane comprising: A step S1 of providing an initial alloy, the composition of said initial alloy being RE a Al b M cRE is selected from at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; M is selected from at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, and Ti; a, b, and c represent the atomic mass percentage contents of the corresponding composition elements, respectively, and 0.1%≦b≦25%, 0.1%≦c≦35%, and a+b+c=100%; the solidification structure of the initial alloy includes a matrix phase and a dispersed particle phase, and the average composition of the matrix phase is RE. x1 Al y1 The component of the dispersed particle phase is M x2 Al y2 Step S1, where x1, y1, x2, and y2 represent the atomic mass percentage contents of the corresponding composition elements, and 0.5%≦y1≦30%, 0.1%≦y2≦25%, x1+y1=100%, and x2+y2=100%; A step S2 of providing an acid solution, mixing the initial alloy with the acid solution, reacting a matrix phase in the initial alloy with the acid solution to form metal ions, and releasing a dispersed particle phase in the initial alloy to obtain an aluminum-containing alloy powder, wherein the component of the aluminum-containing alloy powder is M x2 Al y2 Step S2, The present invention further provides a method for producing an aluminum-containing alloy powder, comprising:
[0088] In step S1, the initial alloy RE is prepared according to a specific composition and content. a Al b M c Prepare raw materials for smelting. In step S1, said initial alloy is obtained by the following sub-steps: (1) Weigh out the ingredients according to the mixing ratio. (2) The above raw materials are melted to obtain a molten alloy. (3) solidifying the molten alloy to obtain the initial alloy, wherein the solidification rate is 0.001 K / s to 10 7 K / s.
[0089] In the above sub-step (1), if the raw materials are metal M, metal Al and rare earth RE, the elements can be melted according to the mixing ratio to prepare the above initial alloy melt. If the alloy raw materials provided are directly RE, a Al b M c If it is an alloy, RE a Al b M c The alloy is remelted to obtain an alloy melt. Of course, metal M, metal Al, and rare earth RE are melted to obtain RE. a Al b M c The alloy was prepared and further RE a Al b M c The alloy may also be remelted to obtain an alloy melt.
[0090] In the above sub-step (3), the solidification method is not limited to the above, and may be a casting method, a melt strip casting method, a melt drawing method, etc. The particle size and morphology of the finally formed alloy powder are determined by the composition of the initial alloy. x2 Al y2 The particle size and morphology of the dispersed particle phase are almost identical to those of the above-mentioned components, x2 Al y2 The particle size of the dispersed particle phase, which is M, is related to the solidification rate of the alloy melt during manufacturing. x2 Al y2 The particle size of the dispersed particle phase is negatively correlated with the cooling rate of the alloy melt, that is, the faster the solidification rate of the alloy melt, the smaller the particle size of the dispersed particle phase. 7 K / s, whereby the components in the initial alloy are M x2 Al y2 The particle size of the dispersed particle phase is set to 2 nm to 50 mm, and aluminum-containing alloy powders with different morphologies on the nano-order, submicron-order, micron-order, and millimeter-order are produced.
[0091] In the sub-step (3), the solidification structure of the initial alloy obtained by solidifying the alloy melt includes a matrix phase and a dispersed particle phase, and the dispersed particle phase is a particle phase dispersed and distributed in the matrix phase, and the average component of the matrix phase is RE x1 Al y1 The component of the dispersed particle phase is M x2 Al y2 and the component is M x2 Al y2 The small amount of Al dissolved in the dispersed particle phase is protected by the inert element M and is less likely to react with the acid solution. x1 Al y1 The matrix phase, which is an active component, is highly reactive with acids. Therefore, the solidification structure of the initial alloy is favorable for subsequent separation, and the component M x2 Al y2 It is advantageous to obtain an aluminum-containing alloy powder in which
[0092] Furthermore, the average content of Al element is RE x1 Al y1 The atomic mass percentage content for the matrix phase is x2 Al y2 is higher than the atomic mass percentage content for the dispersed particle phase that is y1>y2.
[0093] Furthermore, the particle shape of the dispersed particle phase is not limited and may include at least one of dendritic, spherical, approximately spherical, rectangular, discoid, and rod-shaped. When the particle shape is rod-shaped, the particle dimensions refer specifically to the diameter dimension of the rod-shaped cross section.
[0094] Furthermore, the particle size of the dispersed particle phase is from 2 nm to 50 mm.
[0095] Furthermore, the acid in the acid solution contains at least one of sulfuric acid, hydrochloric acid, nitric acid, perchloric acid, phosphoric acid, acetic acid, oxalic acid, formic acid, and carbonic acid, and the molar concentration of the acid is 0.001 mol / L to 20 mol / L.
[0096] Furthermore, the solvent in the acid solution includes water.
[0097] Furthermore, the reaction temperature between the matrix phase and the acid solution is 0° C. to 100° C., and the reaction time is 0.1 min to 24 hours.
[0098] Furthermore, after the reaction step of the matrix phase with the acid solution, a step of screening the released pre-prepared powder and then subjecting each to plasma spheroidizing treatment to obtain spherical aluminum-containing alloy powders having different particle sizes may be further carried out, or a step of subjecting the released pre-prepared powder to plasma spheroidizing treatment and screening to obtain spherical aluminum-containing alloy powders having different particle sizes may be further carried out.
[0099] Furthermore, the aluminum-containing alloy powder obtained by the above-mentioned production method is used in optoelectronic devices, electromagnetic wave absorbing materials, catalysts, three-dimensional metal printing, metal injection molding, and anticorrosive paints.
[0100] Furthermore, the use of the aluminum-containing alloy powder obtained by the above production method for three-dimensional metal printing, characterized in that the aluminum-containing alloy powder has a particle size of 0.5 μm to 1 mm.
[0101] Furthermore, the present invention relates to a method for producing an aluminum-containing alloy powder, the method comprising the steps of: forming an aluminum-containing alloy powder having a particle size of 0.1 μm to 50 μm; and using the aluminum-containing alloy powder for metal injection molding.
[0102] Furthermore, the present invention relates to use of the aluminum-containing alloy powder obtained by the above-mentioned production method in an anticorrosive coating, the aluminum-containing alloy powder having a particle size of 2 nm to 5 μm.
[0103] The method for producing an aluminum-containing alloy powder according to the present invention has the following advantages:
[0104] First, select metal M, metal Al and rare earth RE of specific type and content, and the components are RE a Al b M cThe solidification structure of the initial alloy is made of the following components: x2 Al y2 The dispersed particle phase is RE x1 Al y1 The structure of the structure is favorable for the dispersed particle phase to be separated by the reaction of the initial alloy with the acid solution. Specifically, when the initial alloy reacts with the acid solution, the hydrogen ions in the acid solution react with the rare earth elements and aluminum elements in the matrix phase, and the rare earth elements and aluminum elements dissolve and enter the solution as ions. x2 Al y2 The small amount of Al dissolved in the dispersed particle phase is protected by the inert element M and does not react easily with the acid solution. x2 Al y2 The dispersed particle phase has an average composition of RE x1 Al y1 After the matrix phase, which is the matrix phase, reacts with the acid solution and is removed, the components are dispersed and desorbed, and the M x2 Al y2 The particle size of the aluminum-containing alloy powder may be on the order of nanometers, submicrometers, micrometers, or even millimeters.
[0105] Next, since a large amount of rare earth elements are present in the alloy melt obtained by melting the raw materials of the present invention, even if oxygen element enters the alloy melt, it is quickly "absorbed" by the rare earth elements, forming a dense rare earth oxide protective film covering the surface of the alloy melt, and the oxygen element further blocks the passage into the alloy melt, so that the sub-step (2) described in the present invention can melt the raw materials under low vacuum conditions, and even under atmospheric conditions. In addition, the rare earth elements present in the alloy melt not only have a very good "absorption" effect on oxygen element, but also have a very good "absorption" effect on various other impurity elements in the raw materials M and Al. Therefore, the dispersed particle phase in the initial alloy obtained by solidification in the above sub-step (3) is not only not contaminated by oxygen element, but also has a lower impurity element content than the raw materials M and Al. These impurity elements have an average composition of REx1 Al y1 The average component is RE x1 Al y1 The matrix phase is reacted with the acid, and the components are removed by this reaction. x2 Al y2 The aluminum-containing alloy powder having the above formula (I) has a lower impurity content than the raw material M and the raw material Al.
[0106] The manufacturing method of the present invention has a simple process, is easy to operate, is low cost, and can produce high-purity aluminum-containing alloy powders with different morphologies in the nano-order, submicron-order, micron-order, and milli-order, and has great potential for use in the fields of optoelectronic devices, electromagnetic wave absorbing materials, catalysts, three-dimensional metal printing, metal injection molding, anticorrosive coatings, etc. [Brief description of the drawings]
[0107] [Figure 1] FIG. 1 is an energy spectrum diagram of the Ti—V—Al powder of Example 5 of the present invention. [Diagram 2] FIG. 2 is a scanning electron microscope photograph of the Ti—V—Al powder of Example 6 of the present invention. [Diagram 3] FIG. 3 is a scanning electron microscope photograph of the Ti—V—Al powder of Example 7 of the present invention. [Figure 4] FIG. 4 is a scanning electron microscope photograph of the Ti—V—Al powder of Example 8 of the present invention. [Diagram 5] FIG. 5 is an energy spectrum diagram of the Ti—V—Al powder of Example 8 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0108] The preparation method and use of the aluminum-containing alloy powder are further illustrated below with specific examples.
[0109] Example 1: This embodiment provides a method for producing a micron-order Ti-V-Cr-Mo-Zr-Al alloy powder, which includes the following steps: (1) Gd 76 Al 8 (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 16 The raw materials were weighed according to the alloy (atomic mass percentage) composition ratio, and after arc smelting, Gd 76 Al 8 (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 16 A master alloy was obtained. The master alloy was induction melted and reheated to melt it into a molten alloy, and the molten alloy was melted into a Gd alloy having a thickness of 1 mm to 20 mm at a solidification rate of 10 K / s to 1000 K / s. 76 Al 8 (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 16 The solidification structure of the thin alloy plate had an average composition of about Gd 91.5 Al 8.5 The matrix phase is composed of (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 94.5 Al 5.5 and dispersed dendritic particles, and the particle size of the dispersed particle phase was 1 μm to 200 μm. (2) At room temperature, 1 gram of the Gd 76 Al 8 (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 16 The thin alloy plate was added to 150 mL of a 0.25 mol / L sulfuric acid solution to carry out the reaction. During the reaction, the average concentration was about Gd 91.5 Al8.5 The matrix phase reacts with the acid to become ions, which enter the solution, and the micron-order (Ti) particles that are difficult to react with the acid are formed. 82 V 8 Cr 6 Mo 2 Zr 2 ) 94.5 Al 5.5 The dispersed dendritic particle phase gradually separated from the matrix phase and dispersed. After 20 min, the obtained (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 94.5 Al 5.5 The micron particles are separated from the solution, washed and dried to produce micron-order (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 94.5 Al 5.5 The alloy powder was obtained, and the single (Ti 82 V 8 Cr 6 Mo 2 Zr 2 ) 94.5 Al 5.5 The average size range of the particles was from 1 μm to 200 μm.
[0110] Example 2: This embodiment provides a method for producing a micron-order Ti-Mo-Zr-Al alloy powder, which includes the following steps: (1) Ce 76 Al 8 (Ti 98 Mo 1 Zr 1 ) 16 The raw materials were weighed according to the alloy (atomic mass percentage) composition ratio, and after arc smelting, Ce was 76 Al 8 (Ti 98 Mo 1 Zr 1 ) 16A master alloy was obtained. The master alloy was induction melted and reheated to melt it into a molten alloy, and the molten alloy was melted into a Ce alloy having a thickness of 1 mm to 20 mm at a solidification rate of 10 K / s to 1000 K / s. 76 Al 8 (Ti 98 Mo 1 Zr 1 ) 16 The solidification structure of the thin alloy plate had an average composition of about Ce. 91.5 Al 8.5 The matrix phase is composed of (Ti 98 Mo 1 Zr 1 ) 94.5 Al 5.5 and a dispersed dendritic particle phase, and the size of the dispersed particle phase was 1 μm to 200 μm. (2) At room temperature, 1 gram of Ce obtained in step (1) 76 Al 8 (Ti 98 Mo 1 Zr 1 ) 16 The thin alloy plate was added to 200 mL of 0.4 mol / L hydrochloric acid solution to carry out the reaction. During the reaction, the average composition was about Ce. 91.5 Al 8.5 The matrix phase reacts with the acid to become ions, which enter the solution, and the micron-order (Ti) particles that are difficult to react with the acid are formed. 98 Mo 1 Zr 1 ) 94.5 Al 5.5 The dispersed dendritic particle phase gradually separated from the matrix phase and dispersed. After 20 min, the obtained (Ti 98 Mo 1 Zr 1 ) 94.5 Al 5.5 The micron particles are separated from the solution, washed and dried to produce micron-order (Ti 98 Mo 1 Zr 1 ) 94.5 Al 5.5 The alloy powder was obtained, and the single (Ti 98 Mo 1 Zr 1 ) 94.5 Al5.5 The average size range of the particles was from 1 μm to 200 μm.
[0111] Example 3: This embodiment provides a method for producing nano-order Ti-Cr-Al alloy powder, and the method includes the following steps: (1) Ce 72 Al 12 (Ti 97.5 Cr 2.5 ) 16 The raw materials are weighed according to the alloy (atomic mass percentage) composition ratio, induction melted, and then melted. 72 Al 12 (Ti 97.5 Cr 2.5 ) 16 The alloy melt was obtained. The alloy melt was strip-cast by a copper roller. 5 Ce with a thickness of 20μm to 100μm at a speed of 1000K / s 72 Al 12 (Ti 97.5 Cr 2.5 ) 16 The solidification structure of the alloy ribbon had an average composition of about Ce. 87 Al 13 The matrix phase is composed of (Ti 97.5 Cr 2.5 ) 91.5 Al 8.5 and a dispersed particle phase having a size of 10 nm to 200 nm and a substantially spherical shape. (2) At room temperature, 1 gram of Ce obtained in step (1) 72 Al 12 (Ti 97.5 Cr 2.5 ) 16 The alloy ribbon was added to 150 mL of 0.4 mol / L hydrochloric acid solution to carry out the reaction. During the reaction, the average component was Ce. 87 Al 13 The matrix phase reacts with the acid to become ions, which enter the solution, and the nano-order (Ti) 97.5 Cr 2.5 ) 91.5 Al 8.5The dispersed particle phase gradually separated from the matrix phase and dispersed. 97.5 Cr 2.5 ) 91.5 Al 8.5 The nanoparticles are separated from the solution, washed and dried to produce nano-order (Ti 97.5 Cr 2.5 ) 91.5 Al 8.5 The alloy powder was obtained, and the single (Ti 97.5 Cr 2.5 ) 91.5 Al 8.5 The average size range of the particles was from 10 nm to 200 nm.
[0112] Example 4: This embodiment provides a method for producing a micron-order Ti—Nb—Al alloy powder, which includes the following steps: (1) Ce 68 Al 14 (Ti 96 Nb 4 ) 18 The raw materials are weighed according to the alloy (atomic mass percentage) composition ratio, induction melted, and then melted. 68 Al 14 (Ti 96 Nb 4 ) 18 The alloy melt was solidified at a solidification rate of 10K / s to 1000K / s to form a Ce alloy with a thickness of 1mm to 20mm. 68 Al 14 (Ti 96 Nb 4 ) 18 The solidification structure of the thin alloy plate was made of Ce, 85 Al 15 The matrix phase is composed of (Ti 96 Nb 4 ) 90 Al 10 and a dispersed dendritic particle phase, and the size of the dispersed particle phase was 1 μm to 200 μm. (2) At room temperature, 1 gram of Ce obtained in step (1) 68 Al 14 (Ti 96 Nb 4 )18 The thin alloy plate was added to 200 mL of 0.5 mol / L hydrochloric acid solution to carry out the reaction. During the reaction, the average component was Ce. 85 Al 15 The matrix phase reacts with the acid to become ions, which enter the solution, and the micron-order (Ti) particles that are difficult to react with the acid are formed. 96 Nb 4 ) 90 Al 10 The dispersed dendritic particle phase gradually separated from the matrix phase and dispersed. After 20 min, the obtained (Ti 96 Nb 4 ) 90 Al 10 The dendrite micron particles are separated from the solution, washed and dried to produce micron-order (Ti 96 Nb 4 ) 90 Al 10 The alloy powder was obtained, and the single (Ti 96 Nb 4 ) 90 Al 10 The average size range of the particles was from 1 μm to 200 μm.
[0113] Example 5: This embodiment provides a method for producing nano-order Ti-V-Al alloy powder, and the method includes the following steps: (1) Ce 72 Al 10 (Ti 96 V 4 ) 18 The raw materials are weighed according to the alloy (atomic mass percentage) composition ratio, induction melted, and then melted. 72 Al 10 (Ti 96 V 4 ) 18 The alloy melt was obtained. The alloy melt was strip-cast by a copper roller. 5 Ce with a thickness of 20μm to 100μm at a speed of 1000K / s 72 Al 10 (Ti 96 V 4 ) 18 The solidification structure of the alloy ribbon had an average composition of Ce. 88.5 Al11.5 The matrix phase is composed of (Ti 96 V 4 ) 92.5 Al 7.5 and a dispersed particle phase having a size of 10 nm to 300 nm and a substantially spherical shape. (2) At room temperature, 1 gram of Ce obtained in step (1) 72 Al 10 (Ti 96 V 4 ) 18 The alloy ribbon was added to 200 mL of 0.5 mol / L hydrochloric acid solution to carry out the reaction. During the reaction, the average component was Ce. 88.5 Al 11.5 The matrix phase reacts with the acid to become ions, which enter the solution, and the nano-order (Ti) 96 V 4 ) 92.5 Al 7.5 The dispersed particle phase gradually separated from the matrix phase and dispersed. 96 V 4 ) 92.5 Al 7.5 The nanoparticles are separated from the solution, washed and dried to produce nano-order (Ti 96 V 4 ) 92.5 Al 7.5 The alloy powder was obtained, and the single (Ti 96 V 4 ) 92.5 Al 7.5 The average particle size ranged from 10 nm to 300 nm. As shown in Figure 1, it was verified that the alloy powder was composed of Ti, V, and Al elements.
[0114] Example 6: This embodiment provides a method for producing nano-order Ti-V-Al alloy powder, and the method includes the following steps: (1) Ce 68 Al 14 (Ti 96 V 4 ) 18 The raw materials are weighed according to the alloy (atomic mass percentage) composition ratio, induction melted, and then melted. 68Al 14 (Ti 96 V 4 ) 18 The alloy melt was obtained. The alloy melt was strip-cast by a copper roller. 5 Ce with a thickness of 20μm to 100μm at a speed of 1000K / s 68 Al 14 (Ti 96 V 4 ) 18 The solidification structure of the alloy ribbon had an average composition of Ce. 85 Al 15 The matrix phase is composed of (Ti 96 V 4 ) 90 Al 10 and a dispersed particle phase having a size of 10 nm to 300 nm and a substantially spherical shape. (2) At room temperature, 1 gram of Ce obtained in step (1) 68 Al 14 (Ti 96 V 4 ) 18 The alloy ribbon was added to 200 mL of 0.5 mol / L hydrochloric acid solution to carry out the reaction. During the reaction, the average component was Ce. 85 Al 15 The matrix phase reacts with the acid to become ions, which enter the solution, and the nano-order (Ti) 96 V 4 ) 90 Al 10 The dispersed particle phase gradually separated from the matrix phase and dispersed. 96 V 4 ) 90 Al 10 The nanoparticles are separated from the solution, washed and dried, and the nano-order (Ti 96 V 4 ) 90 Al 10 The alloy powder was obtained, and the single (Ti 96 V 4 ) 90 Al 10 The average particle size ranged from 10 nm to 300 nm. 96V 4 ) 90 Al 10 The alloy powder can be used in the field of titanium alloy anticorrosive paint additives.
[0115] Example 7: This embodiment provides a method for producing submicron-order Ti-V-Al alloy powder, which includes the following steps: (1)(La 50 Ce 50 ) 68 Al 14 (Ti 96 V 4 ) 18 The raw materials are weighed according to the alloy (atomic mass percentage) composition ratio, induction melted, and then melted (La 50 Ce 50 ) 68 Al 14 (Ti 96 V 4 ) 18 The alloy melt was obtained by a copper roller strip casting method for about 10 3 ~10 4 The solidification rate is 100μm to 2mm. 50 Ce 50 ) 68 (Ti 96 V 4 ) 18 The solidification structure of the alloy ribbon was made into an alloy ribbon with an average composition of (La 50 Ce 50 ) 85 Al 15 The matrix phase is composed of (Ti 96 V 4 ) 90 Al 10 and a dispersed particle phase having a size of 100 nm to 1.5 μm. (2) At room temperature, 1 gram of (La 50 Ce 50 ) 68 Al 14 (Ti 96 V 4 ) 18The alloy ribbon was added to 200 mL of a 0.4 mol / L sulfuric acid solution and the reaction was carried out. During the reaction, the average composition was (La 50 Ce 50 ) 85 Al 15 The matrix phase reacts with the acid to become ions, which enter the solution, and the submicron-order (Ti) particles that are difficult to react with the acid are 96 V 4 ) 90 Al 10 The dispersed particle phase gradually separated from the matrix phase and dispersed. 96 V 4 ) 90 Al 10 The submicron particles were separated from the solution, washed and dried to obtain submicron-order (Ti 96 V 4 ) 90 Al 10 The alloy powder was obtained, and the single (Ti 96 V 4 ) 90 Al 10 The average size range of the particles was from 100 nm to 1.5 μm.
[0116] Example 8: This embodiment provides a method for producing a micron-order Ti-V-Al alloy powder, which includes the following steps: (1) Ce 68 Al 14 (Ti 96 V 4 ) 18 The raw materials are weighed according to the alloy (atomic mass percentage) composition ratio, induction melted, and then melted. 68 Al 14 (Ti 96 V 4 ) 18 The alloy melt was then heated at a speed of 50K / s to 500K / s to obtain a Ce melt with a thickness of 2mm to 6mm. 68 Al 14 (Ti 96 V 4 ) 18 The solidification structure of the thin alloy plate was made of Ce, 85 Al15 The matrix phase is composed of (Ti 96 V 4 ) 90 Al 10 and a dispersed dendritic particle phase, and the size of the dispersed particle phase was 5 μm to 100 μm. (2) At room temperature, 1 gram of Ce obtained in step (1) 68 Al 14 (Ti 96 V 4 ) 18 The thin alloy plate was added to 200 mL of 0.5 mol / L hydrochloric acid solution to carry out the reaction. During the reaction, the average component was Ce. 85 Al 15 The matrix phase reacts with the acid to become ions, which enter the solution, and the micron-order (Ti) particles that are difficult to react with the acid are formed. 96 V 4 ) 90 Al 10 The dispersed dendritic particle phase gradually separated from the matrix phase and dispersed. After 20 min, the obtained (Ti 96 V 4 ) 90 Al 10 The micron particles are separated from the solution, washed and dried to produce micron-order (Ti) particles as shown in FIG. 96 V 4 ) 90 Al 10 The alloy powder was obtained, and the single (Ti 96 V 4 ) 90 Al 10 The average particle size ranged from 5 μm to 100 μm. As shown in Figure 5, verification revealed that the alloy powder was composed of Ti, V, and Al elements.
[0117] Example 9: This embodiment provides a method for producing spherical micron-order Ti-V-Al alloy powder, which includes the following steps: (1) Ce 68 Al 14 (Ti 96 V 4 ) 18The raw materials are weighed according to the alloy (atomic mass percentage) composition ratio, induction melted, and then melted. 68 Al 14 (Ti 96 V 4 ) 18 The alloy melt was solidified at a solidification rate of 10K / s to 1000K / s to form a Ce alloy with a thickness of 1mm to 20mm. 68 Al 14 (Ti 96 V 4 ) 18 The solidification structure of the thin alloy plate was made of Ce, 85 Al 15 The matrix phase is composed of (Ti 96 V 4 ) 90 Al 10 and a dispersed dendritic particle phase, and the size of the dispersed particle phase was 1 μm to 200 μm. (2) At room temperature, 1 gram of Ce obtained in step (1) 68 Al 14 (Ti 96 V 4 ) 18 The thin alloy plate was added to 200 mL of 0.5 mol / L hydrochloric acid solution to carry out the reaction. During the reaction, the average component was Ce. 85 Al 15 The matrix phase reacts with the acid to become ions, which enter the solution, and the micron-order (Ti) particles that are difficult to react with the acid are formed. 96 V 4 ) 90 Al 10 The dispersed dendritic particle phase gradually separated from the matrix phase and dispersed. After 20 min, the obtained (Ti 96 V 4 ) 90 Al 10 The micron particles are separated from the solution, washed and dried to produce micron-order (Ti 96 V 4 ) 90 Al 10 The alloy powder was obtained, and the single (Ti 96 V 4 ) 90 Al 10 The average size range of the particles was from 1 μm to 200 μm. (3) 0.5 kilograms of the micron-order (Ti 96 V 4 ) 90 Al 10 The alloy powder was collected and screened through 100 mesh, 270 mesh, 1000 mesh, 2000 mesh, and 8000 mesh screens to classify the dendrite particle size ranges into >150μm, 150μm-53μm, 53μm-13μm, 13μm-6.5μm, 6.5μm-1.6μm, and less than 1.6μm (Ti 96 V 4 ) 90 Al 10 The alloy powders were (Ti) with dendritic particle size ranges of 150μm-53μm, 53μm-13μm, and 13μm-6.5μm. 96 V 4 ) 90 Al 10 The alloy powders were selected and further refined by plasma spheroidization technology to produce spherical (Ti) particles with particle sizes ranging from 150 μm to 53 μm, 53 μm to 13 μm, and 13 μm to 6.5 μm. 96 V 4 ) 90 Al 10 The obtained spherical (Ti 96 V 4 ) 90 Al 10 The alloy powders can be used in three-dimensional metal printing and metal injection molding (MIM) applications.
[0118] Example 10: This embodiment provides a method for producing high purity nano Ti-V-Al alloy powder from low purity raw materials, and the method includes the following steps: Sponge Ti, electrolytic V, rare earth Ce, and Al raw materials with atomic mass percentage contents of T (including at least one of O, H, N, P, S, F, and Cl) impurity elements of 3 at.%, 1 at.%, 2.5 at.%, and 0.2 at.%, respectively, were selected. The initial alloy raw materials were fully melted according to a certain mixing ratio, and the atomic mass percentage content components were mainly Ce. 70.5 Al 10 (Ti 96 V4 ) 17 T 2.5 Thus, an initial alloy melt was obtained in which The initial alloy melt was subjected to copper roller strip casting for 10 to 20 minutes. 6 Ce with a thickness of ~20μm at a solidification rate of K / s 70.5 Al 10 (Ti 96 V 4 ) 17 T 2.5 The solidification structure of the alloy ribbon was mainly composed of Ce. 86.5 Al 10.5 T 3 The matrix phase is mainly composed of (Ti 96 V 4 ) 92.25 Al 7.5 T 0.25 Here, the volume percentage of the dispersed particle phase with respect to the alloy ribbon was about 12%, and the particle size range of the dispersed particle phase was 5 nm to 100 nm, and the shape was approximately spherical. The resulting alloy ribbon is, in other words, an alloy ribbon consisting of the intrinsic aluminum-containing alloy powder and the cladding. At room temperature, the above obtained Ce 70.5 Al 10 (Ti 96 V 4 ) 17 T 2.5 The alloy ribbon was reacted with a hydrochloric acid solution with a concentration of 0.5 mol / L. During the reaction, the average composition was mainly Ce. 86.5 Al 10.5 T 3 The matrix phase reacts with the acid to become ions, which enter the solution, and the nano-order (Ti) 96 V 4 ) 92.25 Al 7.5 T 0.25 The dispersed particle phase gradually separated from the matrix phase and dispersed. After 10 min, the dispersed (Ti 96 V 4 ) 92.25 Al 7.5 T 0.25The nanoparticles are separated from the solution, washed and dried under a protective atmosphere to form nano-order (Ti 96 V 4 ) 92.25 Al 7.5 T 0.25 The alloy powder was obtained, the particle size of which was in the range of 5 nm to 100 nm, and the content of T impurities therein was significantly reduced compared to the sponge Ti raw material. Under a protective atmosphere, nano-order (Ti 96 V 4 ) 92.25 Al 7.5 T 0.25 Titanium alloy nano-modified polymer anticorrosive coating was prepared by mixing the alloy powder with epoxy resin and other coating ingredients.
[0119] Example 11: This embodiment provides a method for producing high-purity micron-order Ti—Nb—Al alloy powder from low-purity raw materials, and the method includes the following steps. The sponge Ti, Nb sheet, rare earth Ce, and Al raw materials were selected, with the atomic mass percentage contents of T (including at least one of O, H, N, P, S, F, and Cl) impurity elements being 3 at.%, 1 at.%, 2.5 at.%, and 0.2 at.%, respectively. The initial alloy raw materials were fully melted according to a certain mixing ratio, and the atomic mass percentage contents of the main component were Ce. 67.5 Al 13 (Ti 96 Nb 4 ) 17 T 2.5 Thus, an initial alloy melt was obtained in which The initial alloy melt was strip cast by a copper roller to produce Ce alloy strips with a thickness of ~1 mm at a solidification rate of 300 K / s. 67.5 Al 13 (Ti 96 Nb 4 ) 17 T 2.5 The solidification structure of the alloy ribbon was mainly composed of Ce. 83.2 Al 13.7 T 3.1 The matrix phase is mainly composed of (Ti 96 Nb 4 )89.95 Al 10 T 0.05 The volume percentage of the dispersed particle phase with respect to the alloy ribbon was about 13%, the particle size range of the dispersed particle phase was 0.5 μm to 150 μm, and the shape was mainly dendritic. At room temperature, the above obtained Ce 67.5 Al 13 (Ti 96 Nb 4 ) 17 T 2.5 The alloy ribbon was reacted with a hydrochloric acid solution with a concentration of 0.5 mol / L. During the reaction, the average composition was mainly Ce. 83.2 Al 13.7 T 3.1 The matrix phase reacts with the acid to become ions, which enter the solution, and the micron-order (Ti) particles that are difficult to react with the acid are formed. 96 Nb 4 ) 89.95 Al 10 T 0.05 The dispersed particle phase gradually separated from the matrix phase and dispersed. After 10 min, the dispersed (Ti 96 Nb 4 ) 89.95 Al 10 T 0.05 The particles are separated from the solution, washed and dried under a protective atmosphere to obtain micron-order (Ti 96 Nb 4 ) 89.95 Al 10 T 0.05 The alloy powder obtained had a particle size range of 0.5 μm to 150 μm, and the content of T impurities therein was significantly reduced compared to the sponge Ti raw material. Above (Ti 96 Nb 4 ) 89.95 Al 10 T 0.05 The alloy powder was screened through 270 mesh, 1000 mesh, 2000 mesh, and 8000 mesh screens to classify the powder into dendritic particle sizes ranging from 150 μm to 53 μm, 53 μm to 13 μm, 13 μm to 6.5 μm, 6.5 μm to 1.6 μm, and less than 1.6 μm (Ti 96 Nb 4 )89.95 Al 10 T 0.05 The alloy powders were obtained with dendritic particle sizes ranging from 150 μm to 53 μm, 53 μm to 13 μm, and 13 μm to 6.5 μm. 96 Nb 4 ) 89.95 Al 10 T 0.05 The alloy powders were selected and further prepared into Ti-Nb-Al alloy powders with particle sizes ranging from 150μm to 53μm, 53μm to 13μm, and 13μm to 6.5μm and approximately spherical in shape by plasma spheroidization. The obtained spherical Ti-Nb-Al alloy powders can be used in the fields of three-dimensional metal printing and metal injection molding.
[0120] Example 12: This embodiment provides a method for producing high purity nano Ti-Al alloy powder from low purity raw materials, and the method includes the following steps: Sponge Ti, rare earth Ce, and Al raw materials were selected with atomic mass percentage contents of T (including at least one of O, H, N, P, S, F, Cl) impurity elements of 3 at.%, 2.5 at.%, and 0.2 at.%, respectively, where the sponge Ti further contains 0.5 at.% Mn and the rare earth Ce further contains 0.7 at.% Mg. The initial alloy raw materials are fully melted according to a certain mixing ratio, and the atomic mass percentage content components are mainly (Ce 99.3 Mg 0.7 ) 70.5 Al 10 (Ti 99.5 Mn 0.5 ) 17 T 2.5 The initial alloy melt was cast by a copper roller strip casting method. 6 The solidification rate is 1000 K / s and the thickness is 20 μm. 99.3 Mg 0.7 ) 70.5 Al 10 (Ti 99.5 Mn 0.5 ) 17 T 2.5 The solidification structure of the alloy ribbon was mainly composed of average components (Ce99.3 Mg 0.7 ) 86.5 Al 10.5 T 3 The matrix phase is mainly composed of (Ti 99.5 Mn 0.5 ) 92.25 Al 7.5 T 0.25 The volume percentage of the dispersed particle phase relative to the alloy ribbon was about 12%, the particle size range of the dispersed particle phase was 5 nm to 150 nm, the shape was approximately spherical, and the number of single crystal particles was more than 80% of the total number of particles. The resulting alloy ribbon is, in other words, an alloy ribbon consisting of the intrinsic aluminum-containing alloy powder and the cladding. At room temperature, the above obtained (Ce 99.3 Mg 0.7 ) 70.5 Al 10 (Ti 99.5 Mn 0.5 ) 17 T 2.5 The alloy ribbon was reacted with a hydrochloric acid solution with a concentration of 1 mol / L. During the reaction, the average composition was mainly (Ce 99.3 Mg 0.7 ) 86.5 Al 10.5 T 3 The matrix phase reacts with the acid to become ions, which enter the solution, and the nano-order (Ti) 99.5 Mn 0.5 ) 92.25 Al 7.5 T 0.25 The dispersed particle phase gradually separated from the matrix phase and dispersed. After 10 min, the dispersed (Ti 99.5 Mn 0.5 ) 92.25 Al 7.5 T 0.25 The nanoparticles are separated from the solution, washed and dried under a protective atmosphere to form nano-order (Ti 99.5 Mn 0.5 ) 92.25 Al 7.5 T 0.25The alloy powder is obtained, the particle size of which is in the range of 5nm to 150nm, and the content of T impurity therein is significantly reduced compared to sponge Ti raw material. In addition, the introduction of Mn and Mg into the alloy melt does not cause the formation of intermetallic compounds composed of Ce, Mg and Ti, Mn in the initial alloy ribbon, and does not affect the structural characteristics of the matrix phase and the dispersed particle phase in the alloy ribbon, nor does it affect the rule of reducing the content of impurities in the dispersed particle phase. Under a protective atmosphere, nano-order (Ti 99.5 Mn 0.5 ) 92.25 Al 7.5 T 0.25 Titanium alloy nano-modified polymer anticorrosive coating was prepared by mixing the alloy powder with epoxy resin and other coating ingredients.
[0121] Example 13: This embodiment provides a method for producing high-purity nano-order Ti-V-Al alloy powder from low-purity raw materials, and the method includes the following steps. The sponge Ti, V raw material, rare earth Ce raw material, and Al raw material were selected, with the atomic mass percentage contents of T (including at least one of O, H, N, P, S, F, and Cl) impurity elements being 1.5 at.%, 0.5 at.%, 1.5 at.%, and 0.2 at.%, respectively. The initial alloy raw materials were fully melted according to a certain mixing ratio, and the atomic mass percentage contents of the main component were Ce. 65.6 Al 15 (Ti 96 V 4 ) 18 T 1.4 Thus, an initial alloy melt was obtained in which The alloy melt was strip-cast by a copper roller method for 10 6 K / s~10 7 The main component is Ce, with a thickness of about 30μm to 50μm at a speed of 1000K / s. 65.6 Al 15 (Ti 96 V 4 ) 18 T 1.4 The solidification structure of the alloy ribbon has an average composition of about Ce. 81.5 Al16.5 T 2 The matrix phase is mainly composed of (Ti 96 V 4 ) 89 Al 10.8 T 0.2 and a dispersed particle phase having a size of 5 nm to 250 nm and a substantially spherical shape, and the volume percentage of the dispersed particle phase relative to the alloy ribbon was approximately 15%. The obtained alloy ribbon is an alloy ribbon consisting of an intrinsic aluminum-containing alloy powder and a cladding. 96 V 4 ) 89 Al 10.8 T 0.2 The dispersed particle phase is an intrinsic Al-containing alloy powder, and Ce 81.5 Al 16.5 T 2 The matrix phase is thus a coating. At room temperature, the main component obtained above is Ce. 65.6 Al 15 (Ti 96 V 4 ) 18 T 1.4 The initial alloy ribbon was reacted with a hydrochloric acid solution with a concentration of 0.5 mol / L. During the reaction, the average composition was mainly Ce. 81.5 Al 16.5 T 2 The matrix phase reacts with the acid to become ions, which enter the solution, and the nano-order (Ti) 96 V 4 ) 89 Al 10.8 T 0.2 The dispersed particle phase gradually separated from the matrix phase and dispersed. 96 V 4 ) 89 Al 10.8 T 0.2 The nanoparticles are separated from the solution, washed and dried under a protective atmosphere to form nano-order (Ti 96 V 4 ) 89 Al 10.8 T 0.2The alloy powder was obtained, the particle size of which was in the range of 5 nm to 250 nm, and the content of T impurity therein was significantly reduced compared to that of Ti raw material. Under a protective atmosphere, nano-order (Ti 96 V 4 ) 89 Al 10.8 T 0.2 Titanium alloy nano-modified polymer anticorrosive coating was prepared by mixing the alloy powder with epoxy resin and other coating ingredients.
[0122] Example 14: This embodiment provides a method for producing high-purity submicron-order Fe-Cr-Al alloy powder from low-purity raw materials, and the method includes the following steps. Fe sheet, Cr sheet, rare earth La, and Al raw materials were selected, each with an atomic mass percentage content of T (including at least one of O, H, N, P, S, F, and Cl) impurity element of 0.75 at.%, 0.5 at.%, 2 at.%, and 0.2 at.%, respectively. The initial alloy raw materials were melted sufficiently according to a certain mixing ratio, and the atomic mass percentage content of the main component was La. 46.5 Fe 27 Cr 7 Al 18 T 1.5 Thus, an initial alloy melt was obtained in which The initial alloy melt was strip-cast by a copper roller method for about 10 5 The thickness is about 100 μm at a cooling rate of K / s. The main component is La. 46.5 Fe 27 Cr 7 Al 18 T 1.5 The solidification structure of the thin initial alloy ribbon is mainly composed of Fe. 73.3 Cr 20 Al 6.5 T 0.2 The dispersed particle phase is mainly composed of La 74 Al 24 T 2 The particle size of the dispersed particle phase was in the range of 5 nm to 3 μm, mainly on the submicron order. The alloy ribbon obtained is an alloy ribbon consisting of an intrinsic aluminum-containing alloy powder and a cladding. 73.3 Cr 20 Al 6.5 T 0.2 The dispersed particle phase of La is an intrinsic Al-containing alloy powder. 74 Al 24 T 2 The matrix phase is thus a coating. La with 0.5 mol / L dilute hydrochloric acid 46.5 Fe 27 Cr 7 Al 18 T 1.5 La in thin initial alloy ribbons 74 Al 24 T 2 The matrix phase is reacted and corroded to remove it, and the main component dispersed is Fe 73.3 Cr 20 Al 6.5 T 0.2 The aluminum-containing alloy powder material was obtained, the particle size of which was in the range of 5 nm to 3 μm, and the content of T impurity therein was obviously reduced compared with that of Fe raw material.
[0123] The technical features of the above-described embodiments may be combined in any manner. For the sake of brevity, we have not described all possible combinations of the technical features in the above embodiments, but as long as there is no contradiction in the combinations of these technical features, they should be considered within the scope described in this specification.
[0124] The above-described examples merely show some embodiments of the present invention, and the description is relatively specific and detailed, but this should not be understood as limiting the scope of protection of the invention. However, those skilled in the art can make some modifications and improvements without departing from the concept of the present invention, and all of them belong to the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be compliant with the scope of the attached claims.
Claims
1. Step 1: Selecting an initial alloy raw material, melting the initial alloy raw material according to a blending ratio of the initial alloy components, and obtaining a homogeneous initial alloy melt, the main component of the initial alloy melt being RE a A b M c T d RE includes at least one of Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; M includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, and Ni; T is an impurity element and includes at least one of O, H, N, P, S, F, and Cl; and a, b, c, and d represent the atomic mass percentage contents of the corresponding composition elements, respectively, and are 35%≦a≦99.7%, 0.1%≦b≦25%, 0.1%≦c≦35%, and 0<d≦10%; Step 2 is to solidify the initial alloy melt into an initial alloy ribbon, the solidification structure of the initial alloy ribbon includes a matrix phase and a dispersed particle phase, the melting point of the matrix phase is lower than that of the dispersed particle phase, the dispersed particle phase is coated with the matrix phase, and the average component of the matrix phase is mainly RE x1 A y1 T z1 The dispersed particle phase is mainly composed of M x2 A y2 T z2 Step 2, in which x1, y1, z1, x2, y2, and z2 respectively represent the atomic mass percentage contents of the corresponding composition elements, and 60%≦x1<99.8%, 0.2%≦y1≦30%, 0.05<z1≦30%, 80%≦x2≦99.8%, 0.1%≦y2≦22%, 0.05≦z2≦1.5%, and z2<d≦z1, during the solidification process of the initial alloy melt, the impurity element T in the initial alloy melt is redistributed between the dispersed particle phase and the matrix phase, and enriched in the matrix phase, thereby purifying the dispersed particle phase; The initial alloy ribbon is reacted with an acid solution, the matrix phase in the initial alloy ribbon reacts with the acid to become ions and enter the solution, the dispersed particle phase that does not react with the acid solution is detached from the initial alloy ribbon, and the main component is M x2 A y2 T z2 Step 3 of obtaining an aluminum-containing alloy powder material, 2. A method for producing an aluminum-containing alloy powder comprising the steps of:
2. 2. The method for producing an aluminum-containing alloy powder according to claim 1, wherein the origins of the impurity elements in the initial alloy melt include impurities introduced from the initial alloy raw materials and impurities introduced from the atmosphere or crucible during the smelting process.
3. 2. The method for producing an aluminum-containing alloy powder according to claim 1, wherein the particle size range of the dispersed particle phase is 2 nm to 3 mm.
4. 2. The method for producing an aluminum-containing alloy powder according to claim 1, wherein the number of single crystal particles of the dispersed particles in the initial alloy ribbon is 75% or more of the total number of dispersed particles.
5. 2. The method for producing an aluminum-containing alloy powder according to claim 1, characterized in that y1>y2.
6. 2. The method for producing an aluminum-containing alloy powder according to claim 1, characterized in that 2z2≦z1.
7. 2. The method for producing an aluminum-containing alloy powder according to claim 1, wherein the particles of the aluminum-containing alloy powder material have a particle size range of 2 nm to 3 mm.
8. 2. The method for producing an aluminum-containing alloy powder according to claim 1, further comprising the step of: screening the aluminum-containing alloy powder material; selecting an aluminum-containing alloy powder material having a particle size range of 5 μm to 200 μm; and subjecting the aluminum-containing alloy powder material to a plasma spheroidizing treatment to obtain a spherical aluminum-containing alloy powder.
9. Use of the aluminum-containing alloy powder according to any one of claims 1 to 8 in an electromagnetic wave absorbing material.
10. Use of the aluminum-containing alloy powder according to any one of claims 1 to 8 in a catalyst.
11. Use of the aluminium-containing alloy powder according to any one of claims 1 to 8 in powder metallurgy.
12. Use of the aluminium-containing alloy powder according to any one of claims 1 to 8 for three-dimensional metal printing.
13. Use of the aluminium-containing alloy powder according to any one of claims 1 to 8 in metal injection moulding.
14. Use of the aluminum-containing alloy powder according to any one of claims 1 to 8 in a coating material.
15. An alloy ribbon comprising an aluminum-containing alloy powder and a coating, comprising: The solidification structure of the alloy ribbon includes a matrix phase and a dispersed particle phase, the matrix phase is the coating, the dispersed particle phase is the aluminum-containing alloy powder, the melting point of the coating is lower than that of the aluminum-containing alloy powder, the aluminum-containing alloy powder is coated with the coating, and the average component of the coating is mainly RE. x1 A y1 T z1 The main component of the aluminum-containing alloy powder is M x2 A y2 T z2 where x1, y1, z1, x2, y2, and z2 represent the atomic mass percentage contents of the corresponding composition elements, and 60%≦x1<99.8%, 0.2%≦y1≦30%, 0.05<z1≦30%, 80%≦x2≦99.8%, 0.1%≦y2≦22%, 0.05≦z2≦1.5%, and z2<z1, y1>y2; and RE is Y, La, Ce, P.
1. An alloy ribbon comprising at least one of the following elements: r, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; M comprising at least one of the following elements: W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, Co, and Ni; and T being an impurity element and comprising at least one of the following elements: O, H, N, P, S, F, and Cl.
Citation Information
Patent Citations
Working substance for magnetic refrigerator and its production
JP1987030840A
Amorphous alloy excellent in mechanical strength, corrosion resistance, and workability
JP1991036243A
Gd-BASED PHASE SEPARATING METALLIC AMORPHOUS ALLOY HAVING UNIQUE MAGNETIC PROPERTIES
KR100969862B1
Preparation method for magnetic metallic glass nano-powder
KR101309516B1